To determine if each ordered pair is a solution to the system of equations, we need to substitute the x and y values into the equations and check if they hold true.
1. (-3, 11):
y = -3(-3) - 4
y = 9 - 4
y = 5
9x + 2y = 9(-3) + 2(11)
9x + 22 = -27 + 22
9x + 22 = -5
This does not hold true, so (-3, 11) is not a solution to the system of equations.
2. (1, -7):
y = -3(1) - 4
y = -3 - 4
y = -7
9x + 2y = 9(1) + 2(-7)
9x - 14 = 9 - 14
9x - 14 = -5
This holds true, so (1, -7) is a solution to the system of equations.
3. (2, 6):
y = -3(2) - 4
y = -6 - 4
y = -10
9x + 2y = 9(2) + 2(6)
9x + 12 = 18 + 12
9x + 12 = 30
This does not hold true, so (2, 6) is not a solution to the system of equations.
4. (0, -4):
y = -3(0) - 4
y = 0 - 4
y = -4
9x + 2y = 9(0) + 2(-4)
0 - 8 = 0 - 8
This holds true, so (0, -4) is a solution to the system of equations.
Therefore, the ordered pairs that are solutions to the system of equations are (1, -7) and (0, -4).
For each ordered pair, determine whether it is a solution to the system of equations.
y=-3x-4
9x+2y=-5
(-3, 11)
(1, -7)
(2, 6)
(0, -4)
1 answer